2016
DOI: 10.1590/1516-3180.2016.0035130416
|View full text |Cite
|
Sign up to set email alerts
|

Splenic diffuse red-pulp small B-cell lymphoma associated with hepatitis B virus: a report of two cases

Abstract: CONTEXT: Splenic diffuse red-pulp small B-cell lymphoma is a rare disease, representing less than 1% of all non-Hodgkin lymphomas (NHL). This entity is characterized by involvement of bone marrow sinusoids and peripheral blood. The majority of cases are at an advanced stage when diagnosed. Its pathogenesis is still poorly understood. CASE REPORTS: We report on two patients with chronic non-replicating hepatitis B virus (HBV) who developed splenic diffuse red-pulp small B-cell lymphoma. Both of them were in sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(51 reference statements)
0
7
0
4
Order By: Relevance
“…Recently, some studies have shown coexistence between chronic hepatitis B virus infection and splenic lymphomas, particularly SMZL, suggesting a new etiological association for this neoplasm. Similar to that observed in HCV positive cases, treatment for HBV with antiviral agents is capable of inducing neoplasm remission [23][24][25][26]. SMZL is usually an indolent and chronic disease, with a median overall survival exceeding 10 years [2,15,16,18].…”
Section: Discussionmentioning
confidence: 72%
“…Recently, some studies have shown coexistence between chronic hepatitis B virus infection and splenic lymphomas, particularly SMZL, suggesting a new etiological association for this neoplasm. Similar to that observed in HCV positive cases, treatment for HBV with antiviral agents is capable of inducing neoplasm remission [23][24][25][26]. SMZL is usually an indolent and chronic disease, with a median overall survival exceeding 10 years [2,15,16,18].…”
Section: Discussionmentioning
confidence: 72%
“…Utilizando o mesmo bioestimulante dessa pesquisa, na cultura do girassol, Junqueira et al (2017) observaram relação direta entre o aumento da massa seca de plântulas e da dose do produto, semelhante ao resultado encontrado na temperatura de 20°C. O incremento de massa seca das raízes deve-se a presença de giberelinas que participam ativamente do crescimento das células radiculares (KERBAUY, 2004) e segundo McDonald & Khan (1983), estes hormônios influenciam o metabolismo proteico, aumentando a taxa de síntese de proteínas nas sementes.…”
Section: Resultsunclassified
“…In a retrospective study of 17 cases with SDRPL, liver involvement was reported in 18% of cases while erythematous and pruritic skin papules were seen in 10% of patients [7]. Concurrent chronic hepatitis B infection has also been described in two cases of SDRPL [8].…”
Section: Clinical Presentationmentioning
confidence: 99%